Gothic Landscapes
XV, 315 p. 3 illus.
Keywords: This book is about the ways that Gothic literature has been transformed since the 18th century across cultures and across genres. In a series of essays written by scholars in the field, the book focuses on landscape in the Gothic and the ways landscape both reflects and reveals the dark elements of culture and humanity. It goes beyond traditional approaches to the Gothic by pushing the limits of the definition of the genre. From landscape painting to movies and video games, from memoir to fiction, and from works of different cultural origins and perspectives, this volume traverses the geography of the Gothic revealing the anxieties that still haunt humanity into the twenty-first century.